2022
DOI: 10.3390/ijms24010699
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Proteolysis in Amyloidosis

Abstract: Amyloidoses are a group of diseases associated with deposits of amyloid fibrils in different tissues. So far, 36 different types of amyloidosis are known, each due to the misfolding and accumulation of a specific protein. Amyloid deposits can be found in several organs, including the heart, brain, kidneys, and spleen, and can affect single or multiple organs. Generally, amyloid-forming proteins become prone to aggregate due to genetic mutations, acquired environmental factors, excessive concentration, or post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 141 publications
1
5
0
Order By: Relevance
“… 35 , 36 , 37 , 38 Proteolysis is a hallmark of inflammation in wounds 39 , 40 and it is therefore worth noting that amyloid aggregates are often composed of proteolytic fragments, derived from the degradation of precursor proteins. These fragments display higher amyloidogenic tendency compared to their precursor proteins, 41 a finding that provides an additional link to the LPS-induced amyloid formation in the AWFs observed in this report. Interestingly, a persistent inflammatory milieu can exacerbate amyloidosis, leading to a vicious cycle of inflammation and disease progression.…”
Section: Discussionsupporting
confidence: 66%
“… 35 , 36 , 37 , 38 Proteolysis is a hallmark of inflammation in wounds 39 , 40 and it is therefore worth noting that amyloid aggregates are often composed of proteolytic fragments, derived from the degradation of precursor proteins. These fragments display higher amyloidogenic tendency compared to their precursor proteins, 41 a finding that provides an additional link to the LPS-induced amyloid formation in the AWFs observed in this report. Interestingly, a persistent inflammatory milieu can exacerbate amyloidosis, leading to a vicious cycle of inflammation and disease progression.…”
Section: Discussionsupporting
confidence: 66%
“…One of the typical pathological features of PD is the formation of misfolded protein aggregates (Lewy bodies) of α-synuclein (α-syn), which disrupt factors involved in proteostasis, such as chaperone proteins, the proteasome or autophagy, and eventually lead to the destruction of dopaminergic neurons 4 , 5 . Current drug development efforts aimed at decreasing α-syn aggregation have focused mainly on using different therapeutic antibodies, but these approaches have not resulted in convincing results of disease improvement 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Current drug development efforts aimed at decreasing α-syn aggregation have focused mainly on using different therapeutic antibodies, but these approaches have not resulted in convincing results of disease improvement 3 . However, accumulating evidence has demonstrated that therapies that target α-syn clearance via proteolytic cleavage or autophagy may provide new therapeutic strategies for PD 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Its crystalline structure reveals that the proteolytic pocket is relatively large, being able to accommodate up to 11 amino acid residues [23,24]. Amyloid plaques, composed mainly of β-amyloid peptide, are progressively formed in the brain of Alzheimer's patients, and mutations in three genes cause the early onset of Familial Alzheimer's disease (FAD) by directly increasing the toxic peptide that promotes β-amyloid 42 [25][26][27]. β-Amyloid is the product of the catabolism of a large protein, the β-Amyloid Precursor Protein (APP) [27][28][29].…”
Section: Introductionmentioning
confidence: 99%